Pyrosequencing analysis of bacterial community changes in dental unit waterlines after chlorogenic acid treatment - Li, Na; Cai, Qin-Ming; Hu, Ni-Ya; Jiang, Shu-ling; Chen, Fu-Qing; Hu, Qiao-Qiao; Yang, Fen; He, Chao-Zhu (Frontiers in Cellular and Infection Microbiology, 2024)
Thank you for your suggestion, we use the text line # to mark the modified parts: #6-8 We changed the order of the first and second units.#106-118 We added the reason for using chlorogenic acid as a substitute antimicrobial agent. #140-163 We added a detailed plan for disinfecting dental floss. #179-188 We added a detailed description of sampling time and quantity. #195-202 We added a description of the cfu value statistical method. #204-208 We added a standardized protocol for DNA extraction. #275-283 We added a comparison of the effects of chlorogenic acid and H 2 O 2 as antimicrobial agents. #348-353 We added a description of the increase in relative abundance at five phylum levels. #373-379 We added the reason for drawing a network diagram. #396-398 We added a description of KEGG. #440-447, #462-465 We provided a more detailed description of the genera that changed in DUWL. #523-560 We discussed the genera Bacteroides and Streptococcus.